Understanding and knowledge regarding protein energy malnutrition among mothers of under five children): An efficient review - Kale, Aparna (International Journal of Nursing Research, 2023)
Malnutrition among children is one of the biggest public health problems recognized by UN for achieving Millennium Development Goals (MDG). India having one of the largest child development programs in the world contributes to one-third of world‟s malnourished children. A significant association is observed between child‟s nutritional status and mother‟s education, wealth index, mother‟s nutritional status, size of child at birth, birth order, child‟s age and type of caste/tribe. Malnutrition continues to be a serious problem in most developing countries as it is directly or indirectly associated with most child deaths. Malnutrition among children is one of the biggest public health problems in India. Malnutrition during childhood leads to poor growth and increased risk of mortality and morbidity in later stages of life. Malnourished children experience developmental delays, weight-loss and illness as a result of inadequate intake of protein, calories and other nutrients. Because of that many children may experience one or several macronutrient and micronutrient deficiencies, they are at risk for a variety of short-term and long-term complications Keyword: Millennium Development Goals, Malnutrition, mortality and morbidity, macronutrient and micronutrient deficiencies, Public health problems.